TRADITIONAL INDIGENOUS KNOWLEDGE, CULTURE AND RELIGIOUS PRACTICES OF TRIPURA WITH SPECIAL REFERENCE TO WATER (TWI) - Debbarma, Prof. Sukhendu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the traditional Indigenous knowledge, culture, and religious practices of Tripura, with special reference to water “twi”. For the Borok people, water is not only a physical resource but also a divine, life-giving force connected to spiritual beliefs, rituals, and social customs. Water plays a central role in numerous ceremonies like birth, death, healing, purification, renewal, etc. The water Goddess “Twima” is worshipped to protect communities from water-borne diseases. Water is also tied to various folktales playing its dual symbolism of life and death. The sacred water “Twipora” is an integral part of rituals and traditional healing practices. The most prominent folktales are that of two sisters, Raima and Saima, whose lives are intertwined with water. In this tale, water symbolizes both life and death exploring the themes of love, loss, and transformation, as water plays a central role in submerging the two lovers’ unity, leaving Saima alone. Another significant folktale is about a brother and sister in Chethuang, where the brother falls in love with his own sister, an act condemned by society. In this story, water becomes a vehicle for purification, with the sister using water to cleanse herself and escape her tragic fate. Even many places and villages are named after rivers, such as Twisa Rangchak “golden river”, Twi Jilik “sparkling water”, and Twi Kormo “yellow water” reflecting the deep bond between the land, people, and water. Ultimately, this research is connection between the Borok people and water, illustrating its central role in their worldview, practices, and ongoing relationship with the natural environment.